Color evaluation of VITA Classical tooth shade guides used in clinical practice for years - Dóra Fehér; György Árpád Keskeny; Zsófia Sára Kovács; Ahmad Reza Mohaghegh; Adrienn Pál; Judit Borbély; Péter Hermann (Hungarian Dental Association, 2023)
Shade determination is a crucial part of making aesthetic restorations and is still carried out visually in most cases. The most commonly used VITA Classical (VC) shade guide is made of acrylic. Due to everyday usage and several disinfection cycles, these shade tabs go through discoloration. Our study aims to investigate the extent of discoloration of the VC shade guides, which are regularly used daily at the Department of Prosthodontics at Semmelweis University. A1, A2, A3, C2, C3 and D2 shades were evaluated which are the most common colors of natural dentition. 9 shade tabs of each color (54 in total) were compared to a corresponding new reference shade tabs both visually and digitally. For the digital color comparison, the VITA Easyshade V spectrophotometer was used to extract the L*a*b values for color comparison, every shade tab (the sample shade tabs (54 in total) and the reference shade tabs) were measured 3 times. ΔE values (color difference) were calculated from the measured L*a*b values with the help of the CIEDE 2000 formula. 70.4% of the tested shade guides showed a color difference (above 0.8 ΔE). Unacceptable color differences (above 1.8 ΔE) were found in 32.4% of the tested shade guides. Only 29,6% of the shade guides were under the perceptibility threshold. During the visual comparison, the examiners found color differences in the case of 38 out of 54 shade guides. Acrylic tooth shade guides go through discoloration over time which can lead to clinical failures. The shade guides used on a daily basis in the dental office need to be verified regularly.